2010
DOI: 10.1002/jor.21252
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of recombinant human BMP‐7 bone formation with bmp binding peptide in a rodent femoral defect model

Abstract: Bone morphogenetic binding peptide (BBP) is an 18.5 kDa fragment of a bone matrix protein peptide. A rat femoral defect model was used to test the effect of BBP combined with recombinant human bone morphogenetic protein-7 (rhBMP-7) to induced bone healing. Two doses of BBP (500 and 1000 mg) were tested with two doses of rhBMP-7 (2 and 5 mg), and the results were compared with a positive control (10 mg rhBMP-7). Bone healing was evaluated by radiology, manual palpation, microcomputed tomography, and histology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Twelve weeks after the second operation, rat femurs were collected for X‐ray assessment and manual palpation. All defects of the harvested femurs were palpated after removal of the stainless steel plate (Liao et al ., ). Any gap in the defect was considered to be non‐union.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve weeks after the second operation, rat femurs were collected for X‐ray assessment and manual palpation. All defects of the harvested femurs were palpated after removal of the stainless steel plate (Liao et al ., ). Any gap in the defect was considered to be non‐union.…”
Section: Methodsmentioning
confidence: 99%
“…Enhancing the osteogenic capabilities of bone matrix for the treatment of fractures and segmental bone defects is an active area of research. It is well-known that the use of oligopeptides or growth factors promotes osteogenic cell proliferation and differentiation in vitro and in vivo [ 1 - 4 ]. There are many different pathways in research to address the acceleration of fracture healing.…”
Section: Introductionmentioning
confidence: 99%
“…All animals were cared for in accordance with the regulations of the IACUC under the supervision of licensed veterinarians. The surgical procedures and assessment of the unions were performed according to the methods of Liao et al [13].…”
Section: Methodsmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) are a subgroup of the transforming growth factor-β (TGF-β) superfamily [13,14,15]. Many studies have reported that BMPs can accelerate bone regeneration and fracture healing [14,16].…”
Section: Introductionmentioning
confidence: 99%